2016
DOI: 10.1007/s00199-016-0969-0
|View full text |Cite
|
Sign up to set email alerts
|

Complex stock price dynamics under Max Weber’s spirit of capitalism hypothesis

Abstract: We introduce Max Weber's spirit of capitalism hypothesis into a benchmark Lucas' tree asset pricing model by assuming that economic agents derive direct utility from wealth. We prove the existence of perfect foresight equilibria where the pricedividend ratio displays explosive rational bubble solutions, endogenous periodic cycles and chaotic dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Several theoretical studies also claim that preferences for wealth are useful for understanding asset price behaviour (see Bakshi and Chen (1996), Smith (2001), Boileau and Braeu (2007)). This paper is in line with this latter branch of the literature, and is closely related to Kamihigashi (2008) and Airaudo (2017), which highlight the role of preferences for wealth in the occurrence of expectation-driven asset price fluctuations in a representative agent framework.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Several theoretical studies also claim that preferences for wealth are useful for understanding asset price behaviour (see Bakshi and Chen (1996), Smith (2001), Boileau and Braeu (2007)). This paper is in line with this latter branch of the literature, and is closely related to Kamihigashi (2008) and Airaudo (2017), which highlight the role of preferences for wealth in the occurrence of expectation-driven asset price fluctuations in a representative agent framework.…”
Section: Introductionsupporting
confidence: 75%
“…I focus on the spirit of capitalism (henceforth, SOC) hypothesis developed by Weber (1905), which captures the intrinsic desire for wealth accumulation. 1 Following Zou (1994Zou ( , 1995, I introduce SOC hypothesis through preferences for wealth, and consider a non-seperable utility function between consumption and wealth holdings. Several empirical studies about the saving behaviour of top income households in the United States support the existence of wealth preferences (see Carroll (2000), Dynan et al (2004), Kumhof et al (2015)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Section 2, we brie ‡y motivate the preference for 9 There has recently been a rising interest in macroeconomics for the monetary policy consequences of bubbles (Gali 2014(Gali , 2017 In many of these papers, especially those relying on an OLG structure, the dimensions of heterogeneity necessary to generate a rational bubble are largely orthogonal to the issue of monetary policy under investigation. 10 Relying on parametric examples within an endowment economy, Airaudo (2017) showed that, without additive separability, the preference for wealth can generate extremely complex, and even chaotic, asset price dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…But, this equivalence breaks down when households have a preference for wealth. 3 This makes it possible to obtain a steady state equilibrium that violates the government's no-Ponzi condition. However, in such cases, there must also exist an equilibrium where households do not want to lend to the government beyond its no-Ponzi condition.…”
Section: Introductionmentioning
confidence: 99%